DESAIN PROTOTIPE PADA STARTUP TALENTKU MENGGUNAKAN METODE LEAN UX STARTUP - Arlisa Kumala Rofik; Tri Sagirani; Sri Hariani Eko Wulandari (Program Studi Teknologi Informasi, 2020)
Talentku is a market validation survey based on the user need to connect the students who have talent and want to hone their talents with companies/organizations that need talent for external and internal activities. The company needs a User Interface (UI) and User Experiences (UX) design as a base building platform. Strategies needed to design the UI/UX to run efective and efficient by prioritizing Just in Time Production. So the problem is how to design the UI/UX of my talent platform effectively and efficiently. The solution used to solve the above problem is designing User Interfaces and User Experiences using Lean UX Startup method. This method is pros